2019
DOI: 10.1029/2019ja026835
|View full text |Cite
|
Sign up to set email alerts
|

Field‐Aligned and Horizontal Currents in the Northern and Southern Hemispheres From the Swarm Satellite

Abstract: We present statistical investigation of the high‐latitude ionospheric current systems in the Northern Hemisphere (NH) and Southern Hemisphere (SH) during low (Kp < 2) and high (Kp ≥ 2) geomagnetic activity levels. Nearly 4 years of vector magnetic field measurements are analyzed from the two parallel flying Swarm A and C satellites using the spherical elementary current system method. The ionospheric horizontal and field‐aligned currents (FACs) for each auroral oval crossing are calculated. The distributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 42 publications
6
25
0
Order By: Relevance
“…4a, b compare well to those of previous publications (e.g., Wang et al 2008;Korth et al 2010;Milan et al 2017;He et al 2012;Coxon et al 2014;Carter et al 2016;Laundal et al 2018). Furthermore, the FACs intensity in the northern hemisphere is slightly higher than that in the southern hemisphere, which is consistent with the findings of Coxon et al (2016) and Workayehu et al (2019). Another feature seen here is that the intensity of R1 currents is stronger than for R2 currents at both dawn and Fig.…”
Section: Observationssupporting
confidence: 92%
“…4a, b compare well to those of previous publications (e.g., Wang et al 2008;Korth et al 2010;Milan et al 2017;He et al 2012;Coxon et al 2014;Carter et al 2016;Laundal et al 2018). Furthermore, the FACs intensity in the northern hemisphere is slightly higher than that in the southern hemisphere, which is consistent with the findings of Coxon et al (2016) and Workayehu et al (2019). Another feature seen here is that the intensity of R1 currents is stronger than for R2 currents at both dawn and Fig.…”
Section: Observationssupporting
confidence: 92%
“…The IMF B z dependence of FAC derived from GF1 compares well to those of previous publications (e.g., Wang et al 2008;Korth et al 2010;Milan et al 2017). Furthermore, the intensity of the FACs in the northern hemisphere is slightly higher than that in the southern hemisphere, which is consistent with the finding of Coxon et al (2016) derived from AMPERE data, Laundal et al (2018) and Workayehu et al (2019) derived from Swarm observations, and with Xiong et al (2020) derived from DMSP observations. These plots show that also small amplitudes near the noise level of GRACE-FO data are well accessible when they are applied in a statistical approach.…”
Section: Auroral Field-aligned Currentssupporting
confidence: 90%
“…Hemispheric asymmetry in currents at high latitudes has been reported in several previous studies (Coxon et al, 2016; Green et al, 2009; Huang et al, 2017; Laundal et al, 2016; Milan et al, 2017; Workayehu et al, 2019). Green et al (2009) found larger average currents in the NH than SH using the cross‐track component of magnetic field data measured by Iridium satellites.…”
Section: Introductionsupporting
confidence: 60%
“…The SECS method (Amm et al, 2015; Juusola et al, 2016; Vanhamäki et al, 2020; Workayehu et al, 2019) is used to estimate FAC and horizontal currents. For estimating currents using the Swarm/SECS analysis method, we first discard magnetic data poleward of ±80° geographic latitude, where the longitudinal separation between Swarm A and Swarm C becomes too small for a reliable current estimation using this method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation